Hot trends and impact in permafrost science. (27th April 2020) - Sjöberg, Ylva; Siewert, Matthias B.; Rudy, Ashley C.A.; Paquette, Michel; Bouchard, Frédéric; Malenfant‐Lepage, Julie; Fritz, Michael
Abstract: An increased interest in Arctic environments, mainly due to climate change, has changed the conditions for permafrost research in recent years. This change has been accompanied by a global increase in scientific publications, as well as a trend towards open access publications. We have analyzed abstracts, titles and keywords for publications on permafrost from 1998 to 2017 to identify developments (topics, impact and collaboration) in the field of permafrost research in light of these changes. Furthermore, to understand how scientists build on and are inspired by each other's work, we have (a) developed citation networks from scientific publications on permafrost and (b) conducted an online survey on inspiration in permafrost science. Our results show an almost 400% increase in publications containing the word permafrost in the title, keywords or abstract over the study period, and a strong increase in climate‐change‐related research in terms of publications and citations. Survey respondents ( n = 122) find inspiration not only in scientific journal publications, but to a large extent in books and public outreach materials. We argue that this increase in global‐scope issues (i.e., climate change) complementing core permafrost research has provided new incentives for international collaborations and wider communication efforts.